FRI0445 Efficacy and Safety of Riociguat in Patients with Pulmonary Arterial Hypertension (PAH) Associated with Connective Tissue Disease (CTD): Results from Patent-1 and Patent-2. (9th June 2015) - Denton, C.; Coghlan, J.G.; Ghofrani, H.-A.; Grimminger, F.; He, J.; Riemekasten, G.; Vizza, C.D.; Boeckenhoff, A.; Meier, C.; Nikkho, S.; Pena, J.; Humbert, M.
Abstract : Background: PAH associated with CTD (PAH-CTD) has a worse prognosis than idiopathic/familial PAH (IPAH). Objectives: Here we report a prospective subgroup analysis of patients (pts) with PAH-CTD from the PATENT studies of the soluble guanylate cyclase stimulator, riociguat. Methods: PATENT-1 was a 12-wk, randomized Phase III trial in which pts with PAH received either riociguat individually dose-adjusted up to 2.5 mg tid (2.5 mg–maximum group), riociguat up to 1.5 mg tid (1.5 mg–maximum group; exploratory), or placebo (pbo). The primary endpoint was change from baseline in 6-minute walking distance (6MWD). Long-term safety and survival were assessed during the PATENT-2 open-label extension. Results: In PATENT-1, 111 pts had PAH-CTD (systemic sclerosis [SSc; n=66, including diffuse SSc and limited SSc] non-SSc CTD [n=39], and unspecified CTD [n=6], derived from the medical history using MedDRA preferred terms). Of the overall group of PAH-CTD pts, 71, 15, and 25 were randomized to riociguat 2.5 mg–maximum, riociguat 1.5 mg–maximum, and pbo, respectively. At baseline, mean ± SD 6MWD was 348±70 m in the riociguat 2.5 mg–maximum group and 361±88 m in the pbo group versus 363±69 m in the overall PAH population. At Wk 12, there was an improvement in 6MWD in the 2.5 mg–maximum riociguat group (+18 m) and a deterioration in the pbo group (–8 m) (Figure 1a ; PAH-CTD population; intention-to-treat [ITT], imputed values). Consistent with other studies, the least-squares mean treatment difference between riociguat and pbo (+28 m) was lower than that observed in the overall study population (+36 m). No pts in the riociguat 2.5 mg–maximum group required additional PAH therapy during PATENT-1, compared with 2 pts in the pbo group. At the March 2014 cut-off for PATENT-2, 70 pts with PAH-CTD had been receiving treatment for ≥2 yrs. Figure 1b shows change in 6MWD during PATENT-2 in pts with PAH-CTD. At 2 yrs, mean ± SD 6MWD had increased from PATENT-1 baseline by 25±82 m in pts with PAH-CTD versus 47±85 m in the overall population (ITT; observed values). Survival rates at 1 yr in pts with PAH-CTD, IPAH, and the overall population were 97% (95% CI: 90–99%), 98% (95% CI: 95–99%), and 97% (95% CI: 95–98%), respectively. Survival rates at 2 yrs were 93% in all cohorts (95% CI: 85–97%, 89–96%, and 90–95%, respectively). Riociguat had a similar safety profile in pts with PAH-CTD as observed in the overall population. Conclusions: In pts with PAH-CTD, riociguat was associated with long-term improvements in exercise capacity. The 1- and 2-yr survival rates in riociguat-treated pts with PAH-CTD were high and similar to pts with IPAH. Disclosure of Interest: C. Denton Consultant for: Bayer, Speakers bureau: Novertis, Pfizer, J. Coghlan: None declared, H.-A. Ghofrani Consultant for: Novertis, Pfizer, Speakers bureau: Novertis, Pfizer, F. Grimminger: None declared, J. He: None declared, G. Riemekasten Consultant for: Bayer, Speakers bureau: Bayer, C. Vizza Grant/research support from: Bayer, Actelion, GSK, Novartis, Gilead, Consultant for: Bayer, Actelion, GSK, Utel, A. Boeckenhoff Employee of: Bayer Pharma AG, C. Meier Employee of: Bayer Pharma AG, S. Nikkho Employee of: Bayer Pharma AG, J. Pena Employee of: Bayer Pharma AG, M. Humbert Consultant for: Novartis, Pfizer, GSK, Actelion, Bayer, Speakers bureau: Novartis, Pfizer, GSK, Actelion, Bayer